Exploring the Foundations of Leadership Excellence: A Theoretical Construct Analysis - Baker, Abeer Wadullah; Abbas, Zeyad Ali; Majeed, Yahya; Khattab, Huda Yousif; Khlaponin, Dmytro (Journal of Ecohumanism, 2024)
Background: Effective leadership is essential for the success of any organization. However, the notion of excellent leadership is intricate, with diverse theoretical perspectives proposed. Objective: This paper aims to analyze three prominent leadership theories, namely transformational, servant, and authentic leadership, through a systematic review of literature. Methods: A methodical exploration of peer-reviewed articles was carried out in essential databases to locate literature on the three theories released from 2017 to 2022. Results: Transformational leadership inspires followers through idealized influence, inspirational motivation, intellectual stimulation, and personalized consideration. Servant leadership prioritizes follower interests, serving them first and foremost. Authentic leadership requires self-awareness and relational transparency between leaders and followers. Conclusion: While each theory provides valuable insights, combining elements from all three theories may provide the most comprehensive view of leadership excellence.